Social Competence of an English Lecturer at English Department of Mulawarman University - Kresentia Sartini; Ida Wardani; Desy Rusmawaty (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2019)
This title underlying this study was social competence of a lecturer at English Department of Mulawarman University. The aims of this study were to know the components of social competence of the lecturer and to know the lecturer practice in his teaching activities. This research used descriptive qualitative method. The subject of the research was the lecturer at English Department of Mulawarman University. The technique of collecting data used by the researcher was observation and interview. After collecting the data, they were analyzed through some stages, making field note into written data, classifying the data based on the components of social competence, analyzing the data and interviewing the subject to answer the research problems. From observations it can be seen that lecturers use several components of social competence. In this case the observation that is seen often using self-regulation is management emotions and also often use interpersonal knowledge and skills that read social situations accurately. From the interview results, it appears that the lecturer does prioritize social relations in the classroom so that it is always good and comfortable so that students can go through classes comfortable. The implication of the research was to know that social competence by the lecturer can make good atmosphere in the classroom and students could be more enjoy the class. Even though the lecturer has some shortage in assess and prepared the material before teaching